Bibliometric analysis of glycolysis and prostate cancer research from 2004 to 2024 - Congxu Zhu; Jingjing Yang; Lumei Liu; Bonan Li; Tiansong Sun; Wen Sheng; Qinghu He (Discover Oncology)
Abstract Background Prostate cancer (PCa) ranks as the second most common disease among men and the fourth most prevalent cancer worldwide. Enhanced glycolysis and excessive lactate secretion are recognized as critical factors driving the progression of various cancers. This study systematically investigated the research trends associated with glycolysis in PCa through bibliometric analysis. Method In this study, we conducted a systematic search of the Web of Science and PubMed databases for literature pertaining to the glycolysis of PCa that was published between January 1, 2004, and June 30, 2024. To achieve this objective, we employed CiteSpace software to generate visualizations that illustrate countries/regions, institutions, journals, and keywords. Additionally, we extracted pertinent quantitative data. Furthermore, we utilized VOSviewer software to create a collaboration network map among various journals. Results Between 2004 and 2024, a total of 408 research articles on glycolysis in PCa were published, indicating a consistent upward trend in the annual publication rate. In this field, the United States not only leads in the volume of research papers but also has the highest degree of centrality. The journal "Cancer Research" is recognized as the most influential in the field, whereas "Prostate and Cancer" serves as a significant platform for disseminating research related to glycolysis in PCa. Keyword analysis has identified four primary research directions that have dominated this field over the past two decades. The role of glycolysis and its associated enzymes in PCa underpins this research. Glycolysis has also demonstrated significant clinical value in the diagnosis and prognosis of PCa. Moreover, drugs targeting glycolytic inhibitors and natural products have exhibited therapeutic potential against this disease. By modulating glycolytic mechanisms, there is potential to increase resistance in PCa. Currently, leading research in this area encompasses the application of nanotechnology to PCa glycolysis, the roles of long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) in this metabolic pathway, and the interactions between glycolysis and other biological processes in PCa. Conclusion This study employs bibliometric analysis to provide a comprehensive overview of research on glycolysis in PCa over the past two decades. It highlights the current state of knowledge in this field, identifies key research hotspots, and explores emerging frontiers, particularly nanotechnology, lncRNA, and miRNA, which are driving innovative research directions.